The Dominus Litis Principle and the Public Prosecutor's Interest in Case Control - Achmad Yani; Mispansyah Mispansyah; Ahmad Syaufi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The Public Prosecutor holds a central role in the criminal justice system as the primary controller of the prosecution process. This authority is based on the fundamental principle of Dominus Litis, which literally translates to